2019
DOI: 10.1542/peds.2018-3488
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Mental Health Program Components and Behavior Risk Reduction: A Meta-analysis

Abstract: CONTEXT: Although adolescent mental health interventions are widely implemented, little consensus exists about elements comprising successful models.OBJECTIVE: We aimed to identify effective program components of interventions to promote mental health and prevent mental disorders and risk behaviors during adolescence and to match these components across these key health outcomes to inform future multicomponent intervention development.DATA SOURCES: A total of 14 600 records were identified, and 158 studies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
121
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(131 citation statements)
references
References 52 publications
8
121
0
2
Order By: Relevance
“…The current review indicated that the effectiveness of the 11 programs varied in relation to the individual outcomes of the programs and the period of follow-up. This nding agrees with that of another study, which revealed that programs implemented by teachers were more effective than those implemented by other stakeholders, such as psychiatrists and researchers [64]. This implies that program development should be outcome-dependent and that it should be followed up effectively and e ciently.…”
Section: Discussionsupporting
confidence: 90%
“…The current review indicated that the effectiveness of the 11 programs varied in relation to the individual outcomes of the programs and the period of follow-up. This nding agrees with that of another study, which revealed that programs implemented by teachers were more effective than those implemented by other stakeholders, such as psychiatrists and researchers [64]. This implies that program development should be outcome-dependent and that it should be followed up effectively and e ciently.…”
Section: Discussionsupporting
confidence: 90%
“…Adolescence is thus a critical time to intervene with this vulnerable groupto prevent mental conditions, to promote positive mental health and to strengthen young people's capacity to navigate challenges and protect themselves from risk. Psychosocial interventions have been identified as beneficial when delivered to universal, or general, adolescent populations: these interventions adopt a psychological, behavioural, and/or social approach to improve psychosocial wellbeing and reduce the risk of poor mental health outcomes [24]. Our meta-analysis found that psychosocial interventions that included specific components (emotional regulation, interpersonal skills, mindfulness, assertiveness training, problem solving, stress management, and alcohol and drug education) were associated with more successful programme outcomes for adolescent mental health [24].…”
Section: Discussionmentioning
confidence: 99%
“…In this review, one of the studies did not indicate if there was allocation concealment or random sampling. In the rst review [60], allocation concealment and random sampling were also not done in some studies. In relation to the research designs employed, the current review included studies that utilised both real life setting designs and research setting designs (i.e., RCTs and quasi-experimental designs).…”
Section: Discussionmentioning
confidence: 99%